Full cicada moon - Hilton, Marilyn (New York, New York : Dial Books for Young Readers, an imprint of Penguin Group, 2015)
In 1969 twelve-year-old Mimi and her family move to an all-white town in Vermont, where Mimi's mixed-race background and interest in "boyish" topics like astronomy make her feel like an outsider.
Middle School
Acclerated Reader
Reading Counts!
790
Keywords: Apollo 11 (Spacecraft) -- Juvenile fiction; Multiracial children -- Juvenile fiction; Sex role in children -- Juvenile fiction; Moving, Household -- Juvenile fiction; Astronomy -- Juvenile fiction; Nineteen sixty-nine, A.D. -- Juvenile fiction; Vermont -- Juvenile fiction; Novels in verse; Multiracial people -- Fiction; Sex role -- Fiction; Novels in verse; Historical fiction